Exposure to Brucella Species, Coxiella burnetii, and Trichinella Species in Recently Imported Camels from Sudan to Egypt: Possible Threats to Animal and Human Health - Ragab M. Fereig; Amira M. Mazeed; Ashraf A. Abd El Tawab; Mohamed El-Diasty; Ahmed Elsayed; Raafat M. Shaapan; Abdelbaset E. Abdelbaset; Caroline F. Frey; Bader S. Alawfi; Sarah A. Altwaim; Azzah S. Alharbi; Gamal Wareth (Pathogens, 2024)
Brucellosis and coxiellosis/Q fever are bacterial infections caused by Brucella species and Coxiella burnetii, respectively; camels are highly susceptible to both pathogens. Trichinellosis is a parasitic infection caused by various Trichinella nematode species. Reportedly, camels are susceptible to experimental infection with Trichinella spp., but information on this potential host species is scarce. All three infections are of zoonotic nature and thus of great public health concern. The current study aimed to determine antibodies against the three pathogens in recently imported camels (n = 491) from Sudan at the two main ports for the entrance of camels into southern Egypt using commercial indirect ELISAs. Samples were collected in two sampling periods. The seropositivity rates of Brucella spp., C. burnetii, and Trichinella spp. were 3.5%, 4.3%, and 2.4%, respectively. Mixed seropositivity was found in 1% for Brucella spp. and C. burnetii. Marked differences were found between the two study sites and the two sampling periods for Brucella. A higher rate of seropositivity was recorded in the Red Sea/older samples that were collected between 2015 and 2016 (4.3%, 17/391; odds ratio = 9.4; p < 0.030) than in those collected in Aswan/recent samples that were collected between 2018 and 2021 (0/100). Concerning C. burnetii, samples collected during November and December 2015 had a significantly higher positivity rate than the other samples (13%, 13/100; OD = 4.8; p < 0.016). The same effect was observed for antibodies to Trichinella spp., with samples collected during November and December 2015 showing a higher positivity rate than the other samples (7%, 7/100; OD = 10.9; p < 0.001). This study provides valuable information on the seroprevalence of Brucella spp. and additional novel information on C. burnetii and Trichinella spp. in recently imported camels kept in quarantine before delivery to other Egyptian regions. This knowledge can be utilized to reduce health hazards and financial burdens attributable to brucellosis, Q fever, and trichinellosis in animals and humans in Egypt.